Building Equitable Neuroscience Research Collaborations in Resource-limited Settings - Asukile, Melody T.; Zunt, Joseph R.; Thakur, Kiran T. (Seminars in Neurology, 2024)
The burden of noncommunicable neurological disorders, such as stroke, dementia, and headache disorders, are on the rise in low- to middle-income countries (LMICs), while neuroinfectious diseases remain a major concern. The development of neuroscience research aimed at defining the burden of neurological diseases across the lifespan, as well as optimizing diagnosis and treatment strategies, is fundamental to improving neurological health in resource-limited settings. One of the key factors to advancing neuroscience research in LMICs is the establishment of effective collaborations based on responsible and trustworthy partnerships between local scientists in LMICs and international collaborators. LMIC researchers face many logistical, institutional, and individual level challenges as they embark on their neuroscience research journey. Despite these challenges, there are opportunities for improving LMIC investigator-led research that should focus on human and institutional infrastructure development. With regard to human capacity building, potential areas for offering support include enhancing research methodology training, offering instruction in manuscript and grant-writing, institutionalizing mentorship programs, and providing opportunities to conduct funded, mentored research to disseminate in high-impact journals. The foundational elements required for implementing and optimizing neuroscience research within an institution include an institutional review board, mentorship programs, data management, research administration, and laboratory facilities. This institutional capacity varies significantly across and within countries, and many rely on collaborations with better-resourced institutions to initiate research. Successful equitable collaborations ensure the engagement of all local and international stakeholders, as well as implementation of a self-sustaining long-term program. Building research capacity in LMICs is an essential endeavor that requires ongoing commitment to training independent scientists. As research capacity increases, LMIC institutions and governments should consider developing competitive research grant programs to support innovative studies led by local researchers, foster regional collaborations, and hence create a sustainable and independent neuroscience research environment.
Keywords: research infrastructure; capacity building; international collaboration; neurosciences